Testicular torsion, time is of the essence: a case for testicular preservation - Cios, Klaudia; Kohn, Daniel; Hall, Philip; Mishail, Alek; Louis, Martine (International Surgery Journal, 2023)
Testicular torsion around the spermatic cord causes arterial and venous occlusion, which can lead to swelling, ischemia, and eventually necrosis of the testicle. It is a urologic emergency that requires a time-dependent diagnosis to prevent testicular loss. This is a case report of an atypical presentation of a 15-year-old male with a 5-day history of testicular torsion, that resulted in preservation of testes viability immediately after detorsion and at 4-week follow-up.